Isaiah 24–27: Studies in a Cosmic Polemic - Barker, William D. (Tyndale bulletin, 2009)
A dissertation exploring the background material for Isaiah 24–27 and showing that it functions to describe the eternal cosmic kingship of Yhwh, while condemning Canaanite deities and cult institutions.